2006
DOI: 10.1128/jb.00086-06
|View full text |Cite
|
Sign up to set email alerts
|

The Brucella abortus Cyclic β-1,2-Glucan Virulence Factor Is Substituted with O-Ester-Linked Succinyl Residues

Abstract: Brucella periplasmic cyclic ␤-1,2-glucan plays an important role during bacterium-host interaction. Nuclear magnetic resonance spectrometry analysis, thin-layer chromatography, and DEAE-Sephadex chromatography were used to characterize Brucella abortus cyclic glucan. In the present study, we report that a fraction of B. abortus cyclic ␤-1,2-glucan is substituted with succinyl residues, which confer anionic character on the cyclic ␤-1,2-glucan. The oligosaccharide backbone is substituted at C-6 positions with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 42 publications
(55 reference statements)
2
44
0
Order By: Relevance
“…Moreover, we have previously observed that a B. abortus cgm mutant unable to succinylate glucans produced only neutral C␤G with the same size distribution as the wild-type strain (2).These evidences ruled out the possibility that mutants in the C-terminal region were affected in C␤G modification.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations
“…Moreover, we have previously observed that a B. abortus cgm mutant unable to succinylate glucans produced only neutral C␤G with the same size distribution as the wild-type strain (2).These evidences ruled out the possibility that mutants in the C-terminal region were affected in C␤G modification.…”
Section: Resultsmentioning
confidence: 71%
“…Removal of substituents from the wild-type anionic C␤G fraction recovered from the TLC plates by mild alkaline treatment yielded neutral glucans with the same DP of those of the nonsubstituted fraction, thus indicating that succinylation was not affected by ring size (2). Moreover, we have previously observed that a B. abortus cgm mutant unable to succinylate glucans produced only neutral C␤G with the same size distribution as the wild-type strain (2).These evidences ruled out the possibility that mutants in the C-terminal region were affected in C␤G modification.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…In addition, the backbone of the PGs is substituted at the C-6 positions with an average of two succinyl resides per molecule. Moreover, the succinyl substituents of cyclic β-(1,2)-glucans in B. abortus are known to be necessary for hypo-osmotic adaptation (28). In Family IV, novel PGs substituted with non-sugar residues http://bmbreports.org BMB reports have recently been found in X. campestris, R. solanacearum and R. sphaeroides.…”
Section: Substituents On Pgs and The Occurrence Of Novel Pgsmentioning
confidence: 96%